1990
DOI: 10.1104/pp.94.3.855
|View full text |Cite
|
Sign up to set email alerts
|

Novel Occurrence of Uncommon Polyamines in Higher Plants

Abstract: Diamines and polyamines are ubiquitous components of living cells, and apparently are involved in numerous cellular and physiological processes. Certain "uncommon" polyamines have limited distribution in nature and have been associated primarily with organisms adapted to extreme environments, although the precise function of these polyamines in such organisms is unknown. This article summarizes current knowledge regarding the occurrence in higher plants of the uncommon polyamines related to and including norsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 13 publications
0
29
0
2
Order By: Relevance
“…This universal availability of homospermidine as the essential precursor of the necine base moiety of all PAs may have been a prerequisite for the repeated establishment of this pathway in angiosperm evolution. Elevated levels of homospermidine have been described for only a few plants, which is the reason for it being regarded as a rare polyamine (Kuehn et al, 1990;Hamana et al, 1992Hamana et al, , 1994. Research is in progress to identify and characterize the enzymes responsible for the elevated homospermidine content in those plants.…”
Section: The Single-copy Gene Dhs Was Duplicated Several Timesmentioning
confidence: 99%
“…This universal availability of homospermidine as the essential precursor of the necine base moiety of all PAs may have been a prerequisite for the repeated establishment of this pathway in angiosperm evolution. Elevated levels of homospermidine have been described for only a few plants, which is the reason for it being regarded as a rare polyamine (Kuehn et al, 1990;Hamana et al, 1992Hamana et al, , 1994. Research is in progress to identify and characterize the enzymes responsible for the elevated homospermidine content in those plants.…”
Section: The Single-copy Gene Dhs Was Duplicated Several Timesmentioning
confidence: 99%
“…The basic polyamines are putrescine, spermidine, and spermine, and it has been reported that several plants (1) and bacteria (2) produce a variety of unusual polyamines such as norspermidine. Polyamines are widely distributed from prokaryotic cells (3) to higher plants and animals (4), and polyamines play important roles in a variety of cellular functions, including translation, transcription, and chromatin remodeling.…”
mentioning
confidence: 99%
“…Basic polyamines are putrescine, spermidine, and spermine. In addition, a variety of unusual polyamines has been reported in several plants (1) and bacteria (2). Polyamines are widely distributed from prokaryotic (3) to eukaryotic cells (4) and are found at especially high concentrations in proliferating cells such as cancer cells (5) and bacteria in the exponential growth phase (6).…”
mentioning
confidence: 99%